Development of a New Method of Extraction of Interstitial Water from Low‐Porosity Consolidated Sediments Recovered During Super‐Deep Drilling Projects. Issue 2 (7th December 2015) - Toki, Tomohiro; Masuda, Harue; Rashid, Harunur; Hammerschmidt, Sebastian; Shinjo, Ryuichi
Abstract : During the Integrated Ocean Drilling Program (IODP) Expedition 338, several methods were tested for the extraction of interstitial water in consolidated, low‐porosity deep‐sea sediments from Site C0002 in the Kumano Basin. On the basis of those tests, we propose a modified ground rock interstitial normative determination (GRIND) method of extraction of interstitial water. In separate runs of the new method, sediment samples were ground in a ball mill with either ultrapure water or a solution of HNO3 . The interstitial water was then extracted with a conventional squeezer. Sufficient solution was extracted by this method to analyse most major and a few minor components of interstitial water that were comparable to those previously reported for samples extracted by the conventional squeezing method. The new method requires much smaller amounts of sediment than that of the conventional method and will be useful for analysis of samples recovered during super‐deep drilling programmes. Key Points: A newly developed ground rock interstitial normative determination (GRIND) method for sediment samples is presented. Suitable to determine the porewater chemistry of ultra‐deep sea sediments. Results for the major chemical attributes of porewater (e.g., chlorinity) comparable to those obtained via conventional squeezing used by the IODP.